(untitled) (Citizenship in Action: Extension and Culture Magazine, 2008)
In this article we intend to present the extension activities of the project “Morphofunctional and clinical aspects of the head and neck” developed in the Fluminense Federal University (UFF) and expose its influence in the professional career, increasing fusion with social and biological sciences. It is important to focus first on questions concerning the research and extention relevance in the academic life. Basic information about the project is presented to graduation and post graduation students in the biomedical field, through the link among theory building and research methodology. Another point is qualifying professors, not only the ones in the in graduation courses of UFF, but also those who work in other universities, updating their knowledge in Histology, Embryology and Anatomy, trough theoretical and practical classes. We have focused on the contribution of extention and research activities and the use of laboratory methods to improve the professional career of the students during the graduation on-the-job improvement.